Kultum Pemuda Tersesat: Mengonter Radikalisme di Indonesia Lewat Pelibatan Pemuda Kekinian - Esa Sang Bhagaskara (Jurnal Studi Pemuda, 2022)
Indonesia’s socio-religious context hindered by youth radicalism issue, which later formulated as the use of illegitimate actions as a mean to express their restlessness. Contra-Radicalism then existed as a preventive discourse with Positive Youth Engagement as one of its’ concrete actions. This research elaborates Kultum Pemuda Tersesat (KPT), an alternative religious youth engagement with popular comedy formats as an approach. By using qualitative content analysis method, this research had three key findings which are [1] KPT based its’ engagement with “Islam Cinta” which has a liberal-progressive tendency to counter radicalism discourse with its’ Islamic-conservative tendency. [2] KPT adjusted itself with the trend by utilizing social media to create an emancipate engagement spaces for youth. [3] KPT offered comedy as an alternative approach in religious engagement for youth. Though potential, KPT’s effectiveness for countering radicalism in Indonesia require a further study.